Evaluación de la producción científica y tecnológica traducida en artículos y revistas especializadas en la universidad técnica de Cotopaxi, propuesta de una revista indexada con metodología para su consecución. - Rodríguez Pillajo, Lucio Armando (2016)
El this research was raised under that there is no incentive for the dissemination of journals indexed in the educational, scientific and technological fields, for which the target was raised to he says diagnose the type of scientific and technological production that have been running at the Technical University of Cotopaxi aimed at designing a model of its structure to run in the future this type of production efficiency and quality, for it was emphasized the independent variable assessment is based on the basic concepts and specialized in search of basic information for the analysis of articles and journals published; on the other hand an approach dependent variable that corresponds to articles and journals relating to basic principles of science and technology focused on new innovations was made. As methodological basis is the modality that focuses on qualitative, literature and field; the type of research is descriptive and explanatory, using an established population with teachers, principals and students from the Technical University of Cotopaxi, considering that is a non-experimental methodology, based on the scientific method and deductive hypothetical; as technical survey and as an instrument the questionnaire seeks to obtain truthful and objective of the actors of the research process was applied information. From the hypothesis it is determined that 65% of respondents know about the format for conducting journals indexed in relation to scientific and technological production of teachers and students from the Technical University of Cotopaxi. The beneficiaries of the scheme and structure of articles and journals are indexed students, teachers and authorities, who were oriented timely for posterity write and publish their scope and achievements in his career.